Corporate Governance Rating System in Taiwan with Multi-Criteria Decision Making Methods - Su, Hsin-An (Contemporary management research, 2013)
Corporate governance has been the subject of extensive research due to high-profile scandals associated in well-known companies. Examining the existed governance rating system in Taiwan, we find that little attention has been paid to the role of corporate governance rating systems and the rating scores are poor predictors in predicting the multiple dimensions of firm performance. This study proposes to use multi-criteria decision-making methods, notably SAW, TOPSIS, and VIKOR, as refined scoring models for a corporate governance rating system. The results show that VIKOR, for its ability to obtain more precise scores, outperforms both the existing methodologies and the other two MCDM approaches. [PUBLICATION ABSTRACT]